The Influence of Delivery Service Quality on Customer Satisfaction: (A Case Study of Shopee Express) - Bilkis, Aliyah; Yusran, Husna Leila; Rapilau; Hamid (Yayasan pendidikan dzurriyatul Quran, 2026)
The study focuses on the impact of quality of delivery services on customer satisfaction of users of the Shopee Express due to the increased consumer expectations within the e-commerce logistics industry. The research is expected to find out the dimensions of service quality in relation to level of customer satisfaction and also establish the level to which operational and interpersonal factors affect the perception of the user. It utilized a quantitative approach by using a structured online survey that was sent to the users of Shopee Express, and 92 valid answers were processed using descriptive, validity, reliability, correlation and regression tools. The results indicate that the ratings of service expectation fulfilment were the highest when respondents rated and evaluated the accuracy of delivery and package safety as respondent ratings, whereas interpersonal engagement by couriers was the lowest rated and a service failure aspect. Statistical tests found that the quality of the service plays a major role in customer satisfaction where the correlation is positive and an explanatory power of 72.3 percent. Regression analysis shows that with the improvement in the quality of services, satisfaction increases can be measured. The research comes up with a conclusion that there is need to improve the relational and emotional communication in the delivery interactions in order to build customer trust and loyalty.